Interrogations for Solo Serge - Koutsomichalis, Marinos (My University, 2020)
'Interrogations for solo Serge' is part of the 'Marinos Koutsomichalis è stato eliminato' project, pivoting on the raw output of the EMS' (the Swedish national centre for electronic music and sound art) Serge modular synthesizer. Employing a series of non-compositional stratagems, the artist attempted to 'eliminate' himself so that the machine’s foundational material attributes may be somehow accelerated and foregrounded.